Evaluasi Proyek Perbaikan Ducting Inlet Slc Boiler PT. Semen Indonesia (Persero) Tbk dengan Critical Path Method (CPM) dan S-Curve - M Nadhif Auliya Authon; Wiwik Handayani (Journal of Management and Bussines (JOMB), 2023)
This research aims to help PT. Menara Mas Persada in optimizing time and costs for the Tuban 3 SLC Boiler Inlet Ducting repair project which experienced a delay in work time of up to 75 days than planned. The research method used is a quantitative descriptive approach using data on material prices, labor wages, and images according to the work project list. The results of the research show that the CPM (Critical Path Method) method identified several activities on the critical path that hindered the progress of the project, namely Ducting 3800xPL.8 x 32M, Welding straps PL 10x150, Sandblast 2.5A for saddle duct, Heat resistant Painting 400cc (primer 2x & finish), Erection ducting, and Erection saddle with a total project processing time of 75 days. In conclusion, the optimal time and cost in accelerating the Tuban 3 SLC Boiler Inlet Ducting repair project is with a time duration of 67.5 days and a cost of IDR 3,670,000,000. Keywords: Critical Path Method, Project Delay, Time Schedule